PERAN PLATFORM DIGITAL (E-COMMERCE DAN MEDIA SOSIAL) DALAM PENGEMBANGAN WIRAUSAHA MUDA: SLR - Nafra Kristia Fitri; Yolanda Putri Nami; Sari, Indah; Ganefri; Elfizon; Andrian (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Digital transformation has become a key driver of entrepreneurial development in the modern economy, particularly through the utilization of e-commerce and social media platforms that enable business creation with relatively low capital requirements and broader market access. Despite these opportunities, young entrepreneurs continue to face various challenges, including limited digital literacy, inadequate human resource capabilities, and increasingly intense market competition that demands continuous innovation and adaptability. This study aims to examine the role of digital platforms in supporting the growth of youth entrepreneurship and to identify the benefits and challenges associated with their utilization. The research employed a Systematic Literature Review (SLR) approach guided by the PRISMA 2020 framework, encompassing the stages of identification, screening, eligibility assessment, and study inclusion. Relevant literature was collected from Google Scholar, Scopus, and ScienceDirect, covering publications from 2021 to 2026. The findings reveal that e-commerce and social media significantly contribute to expanding market reach, enhancing promotional effectiveness, strengthening customer engagement, and improving operational efficiency. Furthermore, digital platforms facilitate entrepreneurial innovation and increase business competitiveness in a rapidly evolving digital environment. The study concludes that digital transformation plays a substantial role in fostering the development of youth entrepreneurship. However, maximizing its potential requires continuous improvement in digital competencies, human resource capacity, and supporting infrastructure to ensure sustainable entrepreneurial growth and long-term business resilience.